Electrical property of Methylcellulose/Chitosan-NH4NO3-EC Plasticized Polymer Electrolyte - N.L.M Zazuli; Azwani Sofia Ahmad Khiar (Trans Tech Publications, Switzerland, 2024)
Polymer electrolytes blends of methylcellulose (MC)/chitosan-ammonium triflate (NH4CF3SO3) plasticized with Ethylene Carbonate (EC) were prepared by solution-casting technique. The effect on electrical property was investigated by impedance spectroscopy. Sample with 45 wt% of EC exhibit the highest room temperature conductivity of 2.16 × 10-4 Scm-1. Dielectric data were analyzed for the sample with the highest conductivity.